Revolutionary time and the avant-garde - Roberts, John 1955- (Verso, 2015)
"Since the decidedly bleak beginning of the twenty-first century, art practice has become increasingly politicized. Yet, few sustained defenses of the avant-garde have been put forward. Revolutionary Time and the Avant-Garde is the first book of its kind to look at the legacy of the avant-garde in relation to the deepening crisis of capitalist non-reproduction. An invigorating revitalization of the Frankfurt School legacy, Roberts's book is unique in its penetrating definition and defense of the avant-garde idea, providing a refined conceptual set of tools that critically engages with the most advanced art theorists of our day, such as Hal Foster, Andrew Benjamin, Alain Badiou, Jacques Ranciere, Paolo Virno, Claire Bishop, Michael Hardt, and Toni Negri"--